2014
DOI: 10.11646/phytotaxa.178.2.2
|View full text |Cite
|
Sign up to set email alerts
|

A new section of Silene (Caryophyllaceae) including a new species from South Anatolia, Turkey 

Abstract: Silene section Cryptoneurae (Caryophyllaceae) and S. ertekinii from Western Antalya, Turkey, are described as new taxa on the basis of morphological and molecular investigations. Nuclear ITS and chloroplast rps16 DNA sequences clearly support the recognition of the new section. Inclusiveness and characterization of the new section is discussed and described, and a key for the included species is provided. Diagnostic characters of the new species S. ertekinii are given and its relation to the other species of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…1782 species complex includes a number of highly similar annual species that are found in the Eastern Mediterranean Region, especially southern Anatolia (Coode and Cullen 1967;Erixon and Oxelman 2008;Aydin et al 2014a). A recent study based on six nuclear loci revealed several cryptic species in the group (Toprak et al 2016).…”
Section: Bernard E Pfeil and Zeynep Toprak Are Equal Contributorsmentioning
confidence: 99%
“…1782 species complex includes a number of highly similar annual species that are found in the Eastern Mediterranean Region, especially southern Anatolia (Coode and Cullen 1967;Erixon and Oxelman 2008;Aydin et al 2014a). A recent study based on six nuclear loci revealed several cryptic species in the group (Toprak et al 2016).…”
Section: Bernard E Pfeil and Zeynep Toprak Are Equal Contributorsmentioning
confidence: 99%
“…sect. Atocion Otth, which is restricted to the Eastern Mediterranean, represents an enigmatic group including species with high sequence substitution rates and unclear relationships at both subgeneric and generic levels (Erixon & Oxelman, ; Toprak & al., ); (7) most of the traditionally proposed infrageneric taxa are not supported as monophyletic (Eggens, ; Popp & Oxelman, ; Rautenberg & al., , ; Petri & Oxelman, ; Aydin & al., ).…”
Section: Introductionmentioning
confidence: 97%
“…Silene), but rejected a subsectional division. Several additional sections have been described subsequent to work (e.g., Oxelman, 1995;Lazkov, 1999;Aydin & al., 2014b). Lazkov (2003) classified the Eurasian taxa into 43 sections and 86 series, although most of the series names were neither effectively (ICN Art.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chowdhuri (1957) delimited 44 sections and his taxonomy has been applied by authors of local floras in the Mediterranean region and SW Asia, including Palestine ( Zohary 1966 ), Turkey ( Coode and Cullen 1967 ), the Iranian Highlands ( Melzheimer 1988 ), the Flora Europaea ( Chater et al 1993 ), and Iraq ( Townsend et al 2016 ). There have been several regionally focused studies (e.g., Greuter 1995 , Oxelman and Greuter 1997 ) that amended the taxonomy of Chowdhuri (1957) , and a number of molecular studies (e.g., Oxelman and Lidén 1995 , Desfeux and Lejeune 1996 , Oxelman et al 1997 , Popp and Oxelman 2004 , Eggens 2006 , Eggens et al 2007 , Popp and Oxelman 2007 , Petri and Oxelman 2011 , Rautenberg et al 2012 , Aydin et al 2014a , Naciri et al 2017 ) that revealed the artificial nature of many sections as defined by Chowdhuri (1957) . Jafari et al (2020) outlined a new, revised system taking the phylogenetic information into account.…”
Section: Introductionmentioning
confidence: 99%